Construction of a Digital and Physical Hybrid Simulation Platform for MMC-HVDC Grid With Fault Current Suppression Equipment - Wang, Weiru; Wang, Limeng; Zhu, Bo; Li, Guoqing; Xin, Yechun; Jiang, Shouqi (Frontiers in Energy Research, 2021)
In order to fully study the working characteristics of large-scale power electronic devices in the field of renewable energy delivery, it is imperative to build digital and physical hybrid simulation platforms. A power interface algorithm based on damping impedance is proposed to improve the stability of DC power grid hybrid platforms. Firstly, according to the characteristics of the open-loop transfer function of the damping impedance method, the matching principle between damping impedance at the power interface and equivalent impedance of the physical simulation system is obtained. Secondly, the calculation method of the equivalent impedance of multi-type equipment on the physical side is proposed, and the impedance real-time matching under different working conditions is realized. In order to reduce the simulation error caused by interface delay, a DC voltage interface delay compensation method based on slope prediction is proposed, and a prediction compensation model is established. A digital and physical hybrid platform for a four-terminal flexible DC power grid with DC circuit breakers is built to verify the proposed interface algorithm. The simulation results show that the proposed interface algorithm can effectively compensate for the interface delay and ensure the stable operation of the platform under different conditions.